Analysis of Secondary Level Internal and External Assessment in Mathematics and English in the Schools of Khotang District - Bista Chhetri, Padam Bahadur (DMC Journal, 2025)
This study aims to investigate the relationship between internal and external assessment in Mathematics and English subjects based on grades for students appearing in the Secondary Education Examination (SEE) in Diktel Rupakot Majhuwagadhi Municipality (DRMM), Khotang District, Koshi Province, Nepal. The study employed a quantitative research design. Using Cluster random sampling technique among seven schools out of 24 secondary schools of DRMM.The data have been processed and analyzed using SPSS 16 software. The study found that A larger number of A+ and A grades is noticed in internal/practical assessment, but other grades, B+, B, C+, C, D and NG, are more visible in external assessment of Mathematics and English subjects for SEE. It shows of grade inflation in internal and external assessment. The average GPA of internal assessment is higher than the external assessment in Mathematics and English subjects. Two hypotheses were formulated and tested at p < 0.05, using Pearson-Product product-moment correlation Coefficient. It is found that there is a low degree of positive correlation between internal assessments and external assessments of class 10 Compulsory Mathematics and English subjects for SEE in Khotang district, Nepal. Represented samples were selected so the results cab be generalized through out the municipality. Regular workshops should be organized for the teacher of secondary level school to conduct internal assessment supervision mechanisms, to form to maintain predictive validity of the assessment.